2017
DOI: 10.1002/jhet.2825
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Solid Acid SO42/TiO2 as Catalyst to the Three‐Component Mannich Reaction at Ambient Temperature

Abstract: in Wiley Online Library (wileyonlinelibrary.com). The three-component Mannich reaction of among dimethyl malonate, aromatic primary amine, and aromatic aldehyde was made successfully in the presence of solid acidic catalyst SO 4 2À /TiO 2 , with excellent catalytic activity, as compared to SO 4 2À /γ-Al 2 O 3 and SO 4 2À /ZnO. To the best of our knowledge, SO 4 2À / TiO 2 prepared at varied calcination temperatures can perform different intensities of Lewis and Brønsted acidities. Because of this point, under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In base catalysis, a weak base such as triethylamine bearing a pair of lone electrons captured the active proton from the α‐carbon of dimethyl malonate to be a strong nucleophile, thus attacking the unactivated substituent to obtain the β‐amino ester (Scheme 18b). Comparing the two activation modes, the yield of acid catalysis was higher than that of base catalysis under the same conditions, indicating that the activation energy of the whole reaction catalyzed by acid was lower than that catalyzed by the base [23] …”
Section: Mannich Reaction Of Carboxylic Acids and Their Derivativesmentioning
confidence: 96%
See 1 more Smart Citation
“…In base catalysis, a weak base such as triethylamine bearing a pair of lone electrons captured the active proton from the α‐carbon of dimethyl malonate to be a strong nucleophile, thus attacking the unactivated substituent to obtain the β‐amino ester (Scheme 18b). Comparing the two activation modes, the yield of acid catalysis was higher than that of base catalysis under the same conditions, indicating that the activation energy of the whole reaction catalyzed by acid was lower than that catalyzed by the base [23] …”
Section: Mannich Reaction Of Carboxylic Acids and Their Derivativesmentioning
confidence: 96%
“…Comparing the two activation modes, the yield of acid catalysis was higher than that of base catalysis under the same conditions, indicating that the activation energy of the whole reaction catalyzed by acid was lower than that catalyzed by the base. [23] In 2020, Smita R. Waghmare introduced a novel and efficient NH 4 Cl-catalyzed one-pot reaction of aromatic amines, aromatic aldehydes or their respective imines with malonate esters, synthesizing β-amino esters in excellent yield (60 %-98 %) (Scheme 19). The authors examined the reactions of various imines 98 with malonate esters 99 using ethanol as solvent at room temperature.…”
Section: Symmetric Mannich Reaction Of Carboxylic Acids and Their Der...mentioning
confidence: 99%
“…Shu et al [82] has reported the three-component Mannich reaction of aromatic aldehyde, aromatic primary amine and dimethyl malonate in presence of TiO Scheme 25. Esterification of phthalic anhydride.…”
Section: Mannich Reactionmentioning
confidence: 99%
“…TiO 2 -SO 4 2À catalyzed three-component Mannich reaction (prepared at 200 °C). [82] Scheme 29. Mechanism that explains the β-amino esters formation.…”
Section: Hantzsch Condensationmentioning
confidence: 99%
“…The N‐ Mannich bases derived from NH ‐heterocycles and their derivatives have received significant attention due to their wide range of biological and pharmacological activities . In particular, much interest has centered around N‐ Mannich bases of isatin, and related compounds, which possess a broad spectrum of action including antibacterial , anticonvulsant , anti‐HIV , antifungal , cytotoxic, and anticancer activities.…”
Section: Introductionmentioning
confidence: 99%